SUSILO BAMBANG YUDHOYONO’S SPEECH THE ROLE OF THE MILITARY IN CHANGING THE WORLD: SEMANTIC ANALYSIS - Nurlaila Sari Harahap; Umar Mono; Bahagia Tarigan (Universitas Bengkulu, 2019)
Semantic is a branch of linguistics that is focused on the meaning of being used by almost of all people in conveying particular communication purpose. Such in the context of speech, people are tend to choose particular diction or language which may bring different sense or meaning to the hearer. It is thus necessary to study the meaning semantically for preventing misunderstandings in interpreting the meaning. So then this study explored the used of semantic meaning in Susilo Bambang Yudhoyo’s speech entitled “The Role of Military in a Changing World”. This study focused on associative meaning and conducted by using descriptive qualitative method. The researcher found that there are 131 utterances in SBY’s speech categorized as associative meaning. The results of this study indicate that the associative meaning in SBY’s speech can be realized through contrastive concept and considering the context it used. Furthermore, it is found that the frequently type of associative meaning used in SBY’s speech was affective meaning in amount of 44%.